Ultralong metahewettite CaV6O16·3H2O nanoribbons as novel host materials for lithium storage: Towards high-rate and excellent long-term cyclability. (April 2016) - Zhang, Xiang; Yang, Weiwei; Liu, Jianguo; Zhou, Yong; Feng, Shichao; Yan, Shicheng; Yao, Yingfang; Wang, Gang; Wan, Li; Fang, Chun; Zou, Zhigang
Abstract: The applications of vanadium oxide bronzes as cathode materials for rechargeable lithium-ion batteries are hindered by inferior cyclability and insufficient rate capability, which arised from weak structural stability and sluggish electrochemical kinetics. To address this issue, we incorporate alkaline-earth metals as interlayer materials within the vanadium oxide layered framework, leading to a whole new family of potential Li + intercalated materials with a general formula MV6 O16 ·nH2 O (M=Mg, Ca, Sr, Ba). In these bronze-hydrated compounds, interlayer water can serve as pillars pinning the V–O layers together, coupled with the enhanced divalent cation pillars, maintaining substantial structure stability and leading to excellent long-term stability. Additionally, the interlayer spacing can be further expanded by intercalation of water molecules, offering enhanced Li + diffusion channel and leading to high rate capability. In this family, we fabricate and study the first such candidate, ultralong metahewettite CaV6 O16 ·3H2 O nanoribbons. When evaluated as cathode materials, for the first time, they exhibit high-rate kinetics (103, 78 mA h g −1 at 6 and 10 A g −1, respectively) and excellent long-term cyclability (83.6%, 89.5% capacity retention after 1000 cycles at 2 and 6 A g −1, respectively). The electrode shows optimal cycling stability for vanadate-based cathode materials for LIBs ever reported. Graphical abstract: Ultralong Metahewettite CaV6 O16 ·3H2 O Nanoribbons exhibit excellent long-term cyclability integrated with high-rate kinetics afforded by a synergistic effect between ultralong 1D nanostructures and intercalated Ca ions along with water molecules within the vanadium oxide layered framework. Highlights: Ultralong CaV6 O16 ·3H2 O nanoribbons were successfully fabricated. It shows long-term cyclability and high-rate kinetics as Li-intercalated material. The alkaline-earth metals in V–O may induce a better electrochemical response.